Current Perspectives On Emerging Biomarkers For Rheumatoid Arthritis-Associated Interstitial Lung Disease - Amigues, Isabelle (Open Access Rheumatol, 2019)
Rheumatoid arthritis (RA) is a common systemic autoimmune disease whose fibro-inflammatory manifestations may affect a number of tissues and organs, including the lungs. In fact, interstitial lung disease (ILD) is a leading cause of mortality among patients with RA. RA-related interstitial lung disease (RA-ILD) most often presents in an injury pattern called usual interstitial pneumonia (UIP), which portends a relatively worse prognosis than other less commonly occurring patterns of RA-ILD, like non-specific interstitial pneumonia (NSIP). Biomarkers from serum or bronchoalveolar lavage fluid could aid in the identification of patients at risk for RA-ILD, the detection of patients most likely to develop the UIP pattern of RA-ILD, and the prediction of disease behaviour over time. Notably, the use of highly sensitive serologic biomarkers, including rheumatoid factor (RF) and antibodies targeting cyclic citrullinated peptides, while somewhat specific for RA joint disease, have only limited utility as biomarkers for RA-ILD. Candidate biomarkers for RA-ILD include these and other autoantibodies as well as certain genes and molecules that hold promise as biomarkers in other forms of ILD. In this manuscript, we summarize the state of knowledge on biomarkers for the development and progression of RA-ILD.